Nilai-Nilai Pendidikan Karakter melalui Ekstrakurikuler Tapak Suci di Sekolah Muhammadiyah Program Khusus (PK) Kartasura - Arief Lutsfi Hakim; Nurul Latifatul Inayati (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
Character education covers both what students should study and how they should use moral principles in their everyday lives. Students' character is greatly influenced by their involvement in extracurricular activities. Given the aforementioned issues, the researcher will attempt to investigate in greater detail what character education is taught in the Holy Trap extracurricular, how much the values of character education have been ingrained in the daily conduct of Muhammadiyah Al-Kautsar Junior High School Special Program students, and the variables affecting the degree of internalization of character education values in students participating in the Holy Trap extracurricular. This study is a brief descriptive qualitative field investigation. Research data collection methods include documentation, in-person interviews, and observation. Three steps make up the stages of data analysis are findings or verification, data display, and data reduction. Religion, discipline, responsibility, and social concern are the components of the character education ingrained in the tapak suci extracurricular at SMP Muhammadiyah Al-Kautsar Special Program, according to the study's findings. Students' everyday behavior reflects the character education values that the tapak suci extracurricular taught them. Self-awareness, trainers' role models, and training duration are factors that affect how much character education values are internalized.